2016
DOI: 10.15243/jdmlm.2016.041.709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inoculation and time of application of microbes on growth and yield of soybean (Glycine max (L.) Merrill)

Abstract: Abstracts:The application of inorganic fertilizers continuously can result in hardening of soil, narrowing of soil pores, thus the roots will have difficulty in penetrating soil. Biological properties of soil that decreases could lead to disruption of microorganism activity, so that the decomposition of organic matter of soil become obstructedand soil fertility decline. Therefore, it is advisable to use an alternative to application of microbes, i.e. Rhizobium and effective microorganisms 4 (EM4) that will enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Tinggi tanaman dengan rhizobium dosis 3 gkg -1 tidak berbeda nyata dengan dosis 6 gkg -1 (Tabel 1). Menurut Muslikah et al (2016), pengaruh nyata pada tinggi tanaman karena mikroba yang diaplikasikan mampu mendekomposisi bahan organik sehingga nutrisi yang dibutuhkan untuk pertumbuhan tanaman dapat tersedia. Nyoki (2017) menambahkan bahwa inokulasi rhizobium dapat melepas sel-sel mati ke dalam tanah yang mengandung nutrisi untuk tanaman atau nutrisi molekul kimia yang tidak tersedia yang tidak digunakan tanaman.…”
Section: Hasil Dan Pembahasan Rhizobium Terhadap Pertumbuhan Dan Hasiunclassified
“…Tinggi tanaman dengan rhizobium dosis 3 gkg -1 tidak berbeda nyata dengan dosis 6 gkg -1 (Tabel 1). Menurut Muslikah et al (2016), pengaruh nyata pada tinggi tanaman karena mikroba yang diaplikasikan mampu mendekomposisi bahan organik sehingga nutrisi yang dibutuhkan untuk pertumbuhan tanaman dapat tersedia. Nyoki (2017) menambahkan bahwa inokulasi rhizobium dapat melepas sel-sel mati ke dalam tanah yang mengandung nutrisi untuk tanaman atau nutrisi molekul kimia yang tidak tersedia yang tidak digunakan tanaman.…”
Section: Hasil Dan Pembahasan Rhizobium Terhadap Pertumbuhan Dan Hasiunclassified
“…Previous research has shown that the application of soil microorganisms, such as rhizobium and biological fertilizers, can enhance soybean growth and yield [12]. Studies by Pedrozo et al [13] and Cordeiro and Echer [14] demonstrated that using nitrogen-fixing bacteria inoculants increased soybean productivity.…”
Section: Introductionmentioning
confidence: 99%